A mathematical model for a direct propane phosphoric acid fuel cell - Psofogiannakis, George (University of Ottawa (Canada), 2003)
In direct hydrocarbon fuel cells, a hydrocarbon fuel is oxidised in the anode electrode. This thesis presents a mathematical model to predict the performance of a unit cell that utilises propane as the fuel, oxygen as the oxidant, phosphoric acid as the electrolyte, and platinum as the catalyst, supported on porous carbon electrodes. The phenomena considered include the electrochemical reactions of propane oxidation and oxygen reduction on platinum, the diffusion of the gases in gas-filled electrode pores, the dissolution and diffusion of dissolved gases in liquid-filled electrode pores as well as ionic conduction of protons. The model was based on the multi-layered physical structure of a modern unit fuel cell. The model was first applied to a phosphoric acid fuel cell cathode electrode. Subsequently, the model was applied to a direct propane-oxygen cell. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.; Energy.